Spatial control of cell differentiation in Myxococcus xanthus - Julien, Bryan (The National Academy of Sciences, 2000)
Myxococcus xanthus develops species-specific multicellular fruiting bodies. Starting from a uniform mat of cells, some cells enter into nascent fruiting body aggregates, whereas other cells remain outside. The cells within the fruiting body differentiate from rods into spherical, heat-resistant spores, whereas the cells outside the aggregates, called peripheral cells, remain rod-shaped. Early developmentally regulated genes are expressed in peripheral cells as well as by cells in the fruiting bodies. By contrast, late developmental genes are only expressed by cells within the nascent fruiting bodies. The data show that peripheral cells begin to develop, but are unable to express genes that are switched on later than about 6 h after the start of development. All of the genes whose expression is limited to the fruiting body are dependent on C-signaling either directly or indirectly, whereas the genes that are equally expressed in peripheral rods and in fruiting body cells are not. One of the C-signal-dependent and spatially patterned operons is called dev, and the dev operon has been implicated in the process of sporulation. It is proposed that expression of certain genes, including those of the dev operon, is limited to the nascent fruiting body because fruiting body cells engage in a high level of C-signaling. Peripheral cells do less C-signaling than fruiting body cells, because they have a different spatial arrangement and are at lower density. As a consequence, peripheral cells fail to express the late genes necessary for spore differentiation.